Malaysia collaborative teaching art studio / Mohd Khairulnizam Ramlie, Ahmad Sofiyuddin Mohd Shuib & Nur Faezah Mohd Fahme - Mohd Khairulnizam, Ramlie; Ahmad Sofiyuddin, Mohd Shuib; Nur Faezah, Mohd Fahme (Universiti Teknologi MARA, Perak, 2017)
Collaborative teaching happens when two or more instructors assume liability for arranging, educating, and checking the accomplishment of learners in a class. Every lecturer adds to the class in view of his or her experience and mastery. Especially, since numerous new projects/courses rise out of more than one conventional control, employees think that its important to join their skill keeping in mind the end goal to address the requirements of these courses or projects (Kulynch, 1998). Collaborative teaching can likewise happen when staff cooperates arranging a few classes as "group courses" (Dugan and Letterman, 2008).